Middlebrow modernism : Britten's operas and the great divide - Chowrimootoo, Christopher, 1985- (University of California Press, 2019)
"At publication date, a free ebook version of this title will be available through Luminos, University of California Press's Open Access publishing program. Visit www.luminosoa.org to learn more. This provocative study is situated at the intersection of the history, historiography, and aesthetics of twentieth-century music. It uses Benjamin Britten's operas to illustrate the ways in which composers, critics, and audiences mediated the 'great divide' between modernism and mass culture. Reviving midcentury discussions of the 'middlebrow, ' Christopher Chowrimootoo demonstrates how these works allowed audiences to have their modernist cake and eat it too: to revel in the pleasures of consonance, lyricism, and theatrical spectacle even while enjoying the prestige that came from rejecting them. By focusing on key moments when reigning aesthetic oppositions and hierarchies threatened to collapse, Middlebrow Modernism offers a powerful model for recovering shades of gray in the previously black-and-white historiographies of twentieth-century music"--Provided by publisher